A STUDY ON SYNTACTIC AND SEMANTIC OF COMPOUND WORDS IN THE RECIPE BOOKS - Komalata Manokaran; Ong Shyi Nian; Gan Wen Shuoh (LLDIKTI Wilayah X, 2021)
This study focuses on the syntactic and semantic process of compound words used in the recipe books. This qualitative descriptive study aims to classify the types of compounds and analyse the semantic and syntactic structure of compounds. This study used Lieber’s (2009) theoretical framework of compound words to analyse the data. This study used 40 compound words from selected recipe books. Morphological analysis is used to analyse the compound words, classify the types and the meaning of compound words on the food terms. Based on the samples chosen, mostly hyphenated compounds, attributive compounds and verb compounds were used in the recipe books.